Cover Image. Issue 10 (4th June 2019) - Iraji, Armin; Deramus, Thomas P.; Lewis, Noah; Yaesoubi, Maziar; Stephen, Julia M.; Erhardt, Erik; Belger, Aysneil; Ford, Judith M.; McEwen, Sarah; Mathalon, Daniel H.; Mueller, Bryon A.; Pearlson, Godfrey D.; et al.
Abstract : COVER ILLUSTRATION Brain networks evolve spatially over time. The spatially fluid chronnectome focuses on the variation in spatial patterns at the voxel level within each network. Here red, blue, and green represent three spatial states of the default mode network. Each spatial state represents a distinct spatial pattern of the default mode network.